2019
DOI: 10.1111/ajt.15472
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying lead time bias when estimating patient survival in preemptive living kidney donor transplantation

Abstract: Preemptive kidney transplantation is the preferred initial renal replacement therapy, by avoiding dialysis and reportedly maximizing patient survival. Lead time bias may account for some or all of the observed survival advantage, but the impact of this has not been quantified. Using the Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry, we included adult recipients of living donor kidney transplants during 1998‐2017. Patients were transplanted preemptively (n = 1435) or after receiving up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…These issues hamper direct comparisons between those transplanted preemptively and those transplanted from the dialysis waiting list. 26,27 Nonetheless, our analysis is consistent with studies that question the benefit and fairness of DD preemptive transplantation.…”
Section: Discussionsupporting
confidence: 86%
“…These issues hamper direct comparisons between those transplanted preemptively and those transplanted from the dialysis waiting list. 26,27 Nonetheless, our analysis is consistent with studies that question the benefit and fairness of DD preemptive transplantation.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study aimed to quantify this phenomenon and found no suggestion of patient survival advantage for adult patients undergoing preemptive living donor KT compared with those transplanted within 6 mo of commencing dialysis. 34 In our pediatric population, we mostly found a better graft survival but we did not find a better patient survival because of the low number of deaths. This better graft survival may be explained by the “CKD lead time” mentioned by Irish et al 34 However, to estimate this “CKD lead time,” we would need the glomerular filtration rate at start of KRT, which is not available in the REIN registry.…”
Section: Discussionmentioning
confidence: 63%
“…The health risks associated with dialysis are particularly heightened during the first 3 months after the initiation of this treatment. Previous studies showed longer patient and graft survival in preemptive KTx recipients [14][15][16]. The mortality benefit in preemptive KTx is multifactorial, with the absence of catheter-associated infections and vascular-access-associated complications, and the lower incidence of CV events being the major contributors.…”
Section: Discussionmentioning
confidence: 99%